2019
DOI: 10.1021/acsomega.9b02147
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Morphine and Codeine in the Presence of Ascorbic Acid and Uric Acid and in Human Plasma at Nafion Single-Walled Carbon Nanotube Thin-Film Electrode

Abstract: In clinical settings, the dosing and differential diagnosis of the poisoning of morphine (MO) and codeine (CO) is challenging due to interindividual variations in metabolism. However, direct electrochemical detection of these analytes from biological matrices is inherently challenging due to interference from large concentrations of anions, such as ascorbic acid (AA) and uric acid (UA), as well as fouling of the electrode by proteins. In this work, a disposable Nafion-coated single-walled carbon nanotube netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 60 publications
(162 reference statements)
6
42
0
1
Order By: Relevance
“…This result is in line with a similar passivation study carried out with a Nafion-coated SWCNT electrode in previous research. 29 Furthermore, the electrodes used to measure 50 μM acetaminophen in whole blood (see Table 1 ) were also used to measure 50 μM acetaminophen in PBS. After wiping away the whole blood, washing with a 40 μL drop of PBS, and confirming that the background returns to that of blank PBS, a mean peak current of 1.83 ± 0.09 μM was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in line with a similar passivation study carried out with a Nafion-coated SWCNT electrode in previous research. 29 Furthermore, the electrodes used to measure 50 μM acetaminophen in whole blood (see Table 1 ) were also used to measure 50 μM acetaminophen in PBS. After wiping away the whole blood, washing with a 40 μL drop of PBS, and confirming that the background returns to that of blank PBS, a mean peak current of 1.83 ± 0.09 μM was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…When selectivity is achieved by an anodic shift of the oxidation peak, however, interference from other endogenous chemicals is expected. 29 , 30 Recent reports have shown selective detection of acetaminophen in urine samples and blood serum. These reports, however, also relied on sample processing including liquid–liquid extraction, precipitation of proteins, and centrifugation as well as considerable dilution of the sample matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For MO, values of the first oxidation peak around + 0.4 V are only shown, as it is most frequently used for determining morphine. [9,36,37] Interestingly, no remarkable changes in the sensitivity towards any of the biomolecules were obtained, even though clear physical and chemical changes were observed with XAS and TEM/STEM. Thus, at least in case of detection of PA, MO and OXC, there seems to be no significant difference in the active electrochemical area, whether majority of the Fe nanoparticles are in metallic or in oxidized state in the SWCNT network.…”
Section: Electrochemical Characterizationmentioning
confidence: 93%
“…In fact, we have shown that as-fabricated pristine CNTs are a suitable material for the detection of neurotransmitter dopamine [5,6] and analgesics such as oxycodone, [7] fentanyl, [8] morphine and codeine. [9] The main methods for fabricating CNTs are chemical vapor deposition, electric discharge and laser ablation, where transition metal particles (Co, Fe, Ni) are used for catalyzing the growth of CNTs. [10] Due to the fabrication conditions, assynthesized CNTs typically consist of residual metal particles, as well as a carbonaceous impurities, for example amorphous carbon and graphitic particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation